A Hollow Core‐Sheath Composite Fiber Based on Polyaniline/Polyurethane: Preparation, Properties, and Multi‐Model Strain Sensing Performance. Issue 1 (30th July 2022) - Wu, Yuting; Yan, Tao; Zhang, Keqin; Pan, Zhijuan
Abstract: Flexible strain sensors are gradually developing toward being textile‐shaped and multifunctional. Here, a microfluidic spinning strategy with special designed coaxial‐like needles is developed to fabricate conductive fibers with multi‐model strain sensing properties. The coaxial‐like needle can regulate the fiber's structure and characteristics by adjusting the meeting point of core and sheath solution. First, a polyaniline (PANI)/thermoplastic polyurethane (TPU)‐based blended composite fiber (PTBF) with unique hollow‐porous morphology is prepared. The PTBF fibrous sensors with 30 wt.% PANI obtain a large strain range (50% strain), while the PTBFs with 50 wt.% PANI possess a high sensitivity (gauge factor of 160). On this basis, a PANI/TPU‐based core–sheath composite fiber (PTCF) is fabricated by changing the core and sheath solutions. PTCFs exhibit satisfactory multi‐model strain sensing capabilities, including tensile, bending, and pressure. The results show that the resistance of PTCF is extremely sensitive to tensile deformation. The PTCF‐based fibrous sensor can also detect 0–180° bending strains and 0.1–2 N pressure strains. The multi‐model strain sensor can be used in motion monitoring, gesture discrimination, finger‐pressure recognition, and flexible circuit switches. This work may provide a foundation for the direct integration of fiber‐based strain sensors into smart clothing. Abstract : The flexible hollow‐porous fibers with multi‐model strain sensing properties are developed by using a simple and scalable microfluidic spinning process with specially designed coaxial‐like needles. The fibers can be used in motion monitoring, gesture discrimination, finger‐pressure recognition, and flexible circuit switches. This work may provide a foundation for the direct integration of fiber‐based strain sensors into smart clothing.